Disengagement From Gangs as Role Transitions. (June 2014) - Decker, Scott H.; Pyrooz, David C.; Moule, Richard K.
<x xml:space="preserve">Abstract</x> Most research has focused on the onset and consequences of gang membership, neglecting the importance of leaving the gang. Disengagement from gangs often occurs during the transition to adulthood, a critical period of the life course. While leaving gangs has received growing attention over the past decade, absent from this research has been a suitable theoretical perspective with which to frame disengagement. This study drew on Ebaugh's theory of role exit to examine disengagement among 260 former gang members. We find disengagement to be a drawn‐out process, replete with many failures and obstacles. We conclude with a discussion of these implications for practitioners, policymakers, and future research.